2016
DOI: 10.1016/s0016-5085(16)30549-2
|View full text |Cite
|
Sign up to set email alerts
|

658 Marine Omega-3 Polyunsaturated Fatty Acid Intake and Survival After Colorectal Cancer Diagnosis

Abstract: Objective-Experimental evidence supports an antineoplastic activity of marine omega-3 polyunsaturated fatty acids (ω-3 PUFAs; including eicosapentaenoic acid, docosahexaenoic acid, and docosapentaenoic acid). However, the influence of ω-3 PUFAs on colorectal cancer (CRC) survival is unknown. AUTHOR CONTRIBUTIONSDrs Song and Chan have full access to all of the data in the study, and take responsibility for the integrity of the data and the accuracy of the data analysis. HHS Public AccessAuthor manuscript Gut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
5
2
1
Order By: Relevance
“…In contrast with the positive findings in the tumor marker‐stratified analysis, we did not find any association between higher MO3PUFA intake and survival in the overall cohort. This observation contrasts with our previous reports that higher intake of MO3PUFA after diagnosis was associated with better survival in two independent cohorts that include stages I–III CRC and stage III colon cancer only, respectively. One of the reasons may be related to the brief FFQ used in the current study, which included only two questions about fish intake and did not specifically inquire about dark‐meat fish (e.g., mackerel, salmon, and sardines) that contains much higher MO3PUFA and is the major source of MO3PUFA intake in the United States .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast with the positive findings in the tumor marker‐stratified analysis, we did not find any association between higher MO3PUFA intake and survival in the overall cohort. This observation contrasts with our previous reports that higher intake of MO3PUFA after diagnosis was associated with better survival in two independent cohorts that include stages I–III CRC and stage III colon cancer only, respectively. One of the reasons may be related to the brief FFQ used in the current study, which included only two questions about fish intake and did not specifically inquire about dark‐meat fish (e.g., mackerel, salmon, and sardines) that contains much higher MO3PUFA and is the major source of MO3PUFA intake in the United States .…”
Section: Discussioncontrasting
confidence: 99%
“…Substantial data support that marine ω‐3 polyunsaturated fatty acids (MO3PUFAs) (i.e., eicosapentaenoic acid [EPA], docosahexaenoic acid [DHA], and docosapentaenoic acid [DPA]) have potential anticancer effects and may improve CRC survival through modulation of local and systemic immune response . Consistent with the mechanistic data, we recently reported that higher intake of MO3PUFA after diagnosis was associated with better survival among patients with established CRC in two independent cohort studies . Furthermore, a phase II randomized placebo‐controlled trial showed that preoperative treatment with MO3PUFA conferred survival benefits among patients with CRC liver metastases .…”
Section: Introductionsupporting
confidence: 55%
“…Of note, previous observational data regarding the favorable influence of other lifestyle factors on CRC survival have been subsequently confirmed in randomized trials. For example, in support of the beneficial association with CRC survival for physical activity 60 and high intake of vitamin D 61 and marine omega-3 fatty acid 62 in prospective cohort studies, randomized clinical trials have documented a positive influence of exercise intervention on patients’ quality of life and functional capacity; 6366 the benefit of preoperative omega-3 fatty acid therapy on reducing tumor vascularity and prolonging patients’ survival; 67 and the effect of high-dose vitamin D supplementation on improved survival in metastatic CRC patients. 68 These robust data indicate the critical role of prospective observational studies in identification of modifiable lifestyle factors for improvement of cancer survival.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to dietary chemoprevention, a plethora of published reports indicate a protective effect of fish oil and its bioactive components, n-3 polyunsaturated fatty acids (PUFA) e.g., eicosapentaenoic acid (20:5Δ5,8,11,14,17) and docosahexaenoic acid (DHA;22:6Δ 4,7,10,13,16,19), with respect to colon cancer risk 46 . In contrast, dietary lipids rich in n-6 PUFA [found in vegetable oils; e.g., linoleic acid (LA;18:2Δ 9,12) and arachidonic acid (20:4Δ 5,8,11,14)] have been linked to an increase in colon tumor development 710 .…”
Section: Introductionmentioning
confidence: 99%